2016
DOI: 10.1039/c6cp06154k
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of cross-effect dynamic nuclear polarization in rotating solids: advantages of elevated temperatures

Abstract: Dynamic nuclear polarization exploits electron spin polarization to boost signal-to-noise in magic-angle-spinning (MAS) NMR, creating new opportunities in materials science, structural biology, and metabolomics studies. Since protein NMR spectra recorded under DNP conditions can show improved spectral resolution at 180-200 K compared to 110 K, we investigate the effects of AMUPol and various deuterated TOTAPOL isotopologues on sensitivity and spectral resolution at these temperatures, using proline and reprodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
36
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 29 publications
5
36
2
Order By: Relevance
“…It has been demonstrated that the DNP signal enhancement observed for membrane samples depends on the nature and concentration of biradicals, the membrane lipid composition [37] and water content [35,43], the protocol of membrane reconstitution ( [35], Figs. 1 and 4), the rotors (Table 1) and/or the support used to orient membranes [49], the DNP/NMR probe [49] and the sample temperature ( [49,[67][68][69] , Fig, 3B).…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that the DNP signal enhancement observed for membrane samples depends on the nature and concentration of biradicals, the membrane lipid composition [37] and water content [35,43], the protocol of membrane reconstitution ( [35], Figs. 1 and 4), the rotors (Table 1) and/or the support used to orient membranes [49], the DNP/NMR probe [49] and the sample temperature ( [49,[67][68][69] , Fig, 3B).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we, 89 as well as others, 22,90 have shown that the performance of a biradical polarizing agent could be improved by deuteration. Two hypotheses were proposed to explain this phenomenon.…”
Section: B Biradical Deuterationmentioning
confidence: 93%
“…Commercial instrumentation operating at magnetic fields from 9.4 to 21.1 T has enabled the use of DNP technology by multiple NMR groups across the globe. Today, DNP MAS NMR is used in structural studies of a broad range of biological sys-tems, including soluble proteins (Jeon et al, 2019), amyloid fibrils and nanocrystals (Bayro et al, 2011;Debelouchina et al, 2013;Frederick et al, 2017;van der Wel et al, 2006;Debelouchina et al, 2010), membrane proteins Cheng and Han, 2013;Tran et al, 2020;Salnikov et al, 2017;Smith et al, 2015;Wylie et al, 2015), nucleic acids (Wenk et al, 2015), viruses and viral protein assemblies (Gupta et al, 2016;Jaudzems et al, 2018;Gupta et al, 2019;Lu et al, 2019;Rosay et al, 2001;Sergeyev et al, 2011), biomaterials (Koers et al, 2013;Ravera et al, 2015;Viger-Gravel et al, 2018), unfolded and misfolded proteins (König I. V. Sergeyev et al: DNP-NMR transfer pathways in HIV-1 capsid assemblies et al, 2019), and intact cells (Viennet et al, 2016;Albert et al, 2018;Judge et al, 2020;Yamamoto et al, 2015), including at natural isotopic abundance (Viger-Gravel et al, 2018;Takahashi et al, 2012). The key advantage of DNP-enhanced MAS NMR is the tremendous sensitivity enhancements afforded by the transfer of polarization from electron spins to nuclear spins.…”
Section: Introductionmentioning
confidence: 99%